Prognosis of Postviral Olfactory Loss: Follow-up Study for Longer than One Year. Issue 5 (September 2014) - Lee, Doh Young; Lee, Woo Hyun; Wee, Jee Hye; Kim, Jeong-Whun
Background: There have been very few studies on the prognosis of postviral olfactory dysfunction. The aim of the study was to evaluate its long-term prognosis and factors influencing the prognosis. Methods: This study included patients who were diagnosed with postviral olfactory dysfunction at least one year ago in a Smell and Taste Clinic and whose telephone interviews were available. Their medical records were reviewed, and they were asked to score their subjective olfactory function on a 100-point scale by telephone interview. Results: A total of 63 patients and 20 normal controls without nasal pathology were included. The mean of the patients was 49.5 years, and 19 males and 44 females were included. The mean length of follow-up was 33.4 months. Olfactory dysfunction was subjectively improved in 85.7% of the patients. The recovery rate to subjective normosmia was 31.7%. The mean symptom scores for smell significantly increased in comparison with baseline from 25.6 to 69.0. Among the 25 patients (37.7%) who underwent follow-up butanol threshold test (BTT), the score improved from 4.6 to 7.3. Olfactory improvement was more frequently reported by females (p = .003) and in patients with follow-up duration for longer than 2 years (p = .043). Conclusions: Follow-up of postviral olfactory loss revealed that over 80% of the patients reported subjective recovery after one year. The more favorable prognosis was associated with longer follow-up duration and female gender.